HAK HADHANAH SETELAH PERCERAIAN (Pertimbangan Hak Asuh bagi Ayah atau Ibu) - Supardi Mursalin (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2015)
The Right of caring a child after divorce: The children should be taken care by their parent,and the parent by all means is responsible to fulfill the need of their children according the parent’sincome ability. In case of divorce between husband and wife, while they still have innocent child, whois more entitled to keep it? Basically after divorce, Islam makes the wife (mother) as the mostimportant person entitled to the rights of children. In addition, there are additional requirements to getthe right namely the ability to maintain of children in religious education and academic, residentialpurposes, the need of food from the source of good and lawful sustenance. If the mother does not meetthe requirements then it will be switch to the other, e.g the father